The Trinity and Christology in The Perspective of Pauline and General Epistles - Keryapi, Donald Steven; Simatupang, Jeslin (Green Publisher Indonesia, 2023)
A true and biblical understanding of the Trinity and Christology must be possessed by every believer. A correct understanding of these two doctrines will certainly affect the life of the personal faith. This study aims to provide a brief understanding of the Trinity and Christology which is specifically highlighted from the perspective of the Apostle Paul's Epistle, General Epistle, and Book of Revelation. This research was carried out because it looked at various theological arguments that emerged and developed, but were very far from the truth of the Bible. This study proceeds from the question of how to understand the Trinity and Christology in Paul's Epistle, General Epistle, and the Book of Revelation. The method used in this study is the descriptive-Bibliological method where researchers make descriptions or descriptions of each point or idea about the Trinity and Christology built from the letters above. The results of this research are expected to contribute to improving the understanding and teaching of the Trinity and Christology, as well as helping believers to deepen their faith. A correct and biblical understanding of the Trinity and Christology will enrich personal faith life and strengthen the foundation of the Christian faith.